-x-2=-4x-29

Simple and best practice solution for -x-2=-4x-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-2=-4x-29 equation:


Simplifying
-1x + -2 = -4x + -29

Reorder the terms:
-2 + -1x = -4x + -29

Reorder the terms:
-2 + -1x = -29 + -4x

Solving
-2 + -1x = -29 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-2 + -1x + 4x = -29 + -4x + 4x

Combine like terms: -1x + 4x = 3x
-2 + 3x = -29 + -4x + 4x

Combine like terms: -4x + 4x = 0
-2 + 3x = -29 + 0
-2 + 3x = -29

Add '2' to each side of the equation.
-2 + 2 + 3x = -29 + 2

Combine like terms: -2 + 2 = 0
0 + 3x = -29 + 2
3x = -29 + 2

Combine like terms: -29 + 2 = -27
3x = -27

Divide each side by '3'.
x = -9

Simplifying
x = -9

See similar equations:

| x^2-212.6x+632550=0 | | 6*x=3 | | -8-3x+7x=-28 | | x-8x+16=0 | | -3(2y-4)=-6 | | -9x+5x-4x=0 | | 3x+8=x+18 | | 49t^2+147t=0 | | -15=x | | 46=-x | | 5x+5y= | | -x=96 | | F=10(x-70)+50 | | 3a-30=-4 | | 0.6(x+7)=24 | | -4=x^3+3x^2-9x-13 | | 3(2y-4)=5(y+3) | | -5=x^3+3x^2-9x-13 | | -4-(-3)= | | -110+22x=-1 | | 3x^2+15x-2=0 | | -16t^2+32t+32=0 | | -8+2x=6 | | -132+11x=-3 | | 4x-10x=36 | | -y+3x+6=-5 | | 3p-2=29 | | 41k=-2747 | | 9y+4y=104 | | 5x+-6=11 | | 29+n=13 | | 4x-9=-9 |

Equations solver categories